EXSTENSIVE READING ROLE IN ENGLISH LANGUAGE TEACHING (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Reading, despite being one of the four essential language learning skills is most often neglected by language learners. This article is primarily concentrated on extensive reading, more precisely the role and the impacts of reading for pleasure is discussed on the example of Uzbekistan State World Languages University.